Brief provider communication skills training fails to impact patient hypertension outcomes. Issue 2 (February 2015) - Manze, Meredith G.; Orner, Michelle B.; Glickman, Mark; Pbert, Lori; Berlowitz, Dan; Kressin, Nancy R.
Highlights We test a provider training to improve patient hypertension outcomes. Training to improve communication skills related to patient-centeredness. The intervention did not improve counseling, adherence or blood pressure outcomes. It may have been too brief and lacked sufficient practice level changes.